Towards a new philosophy: the unpublished writings of K. Satchidananda Murty - Vohra, Ashok; Ramesh, Kotta (Routledge, 2024)
"K. Satchidananda Murty (1924-2011) was a vociferous writer and an iconoclast. This volume is a collection of his unpublished writings It presents Murty's unpublished keynote addresses, papers presented in seminars, and lectures which show his reflections and arguments in contrast to contemporary philosophers with regard to recent developments in philosophy. The writings reveal Murty's rejection of established theories by well-known eastern and western philosophers, as well as his arguments in their support, and present a new interpretation of their contention in the contemporary idiom. Murty critically evaluates the contemporary arguments of Malcolm, James Ross, Alvin Plantinga, Charles Hawthorne, Jean-Paul Sartre, Anthony Flew, E.H. Madden, and P.H. Hare. An important contribution, the book assesses K. Satchidananda Murty's contribution to philosophy during sixty-one years of his engagement with active writing and teaching. It will be of great interest to scholars, teachers, and students of Indian philosophy, Hindu philosophy, Vedāntic philosophy, Advaita Vedānta, comparative philosophy, religious studies, and South Asian studies"--